2003
DOI: 10.1901/jaba.2003.36-205
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis and Treatment of Self‐injurious Behavior in Young Children: A Summary of 30 Cases

Abstract: The assessment and treatment of self-injurious behavior (SIB) has received much attention in the literature; however, few studies have focused on early intervention for this behavior. In the current study, functional analyses with developmentally appropriate modifications were conducted in an outpatient clinic with 30 children (aged 10 months to 4 years 11 months) to assess SIB and problem behavior in its early stages. The reported mean age of SIB onset was 17 months, and head banging was the most prevalent to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
115
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(135 citation statements)
references
References 34 publications
14
115
1
3
Order By: Relevance
“…Behavioral studies show that SIB is largely socially maintained, either by social-positive reinforcementthe provision of favored stimulus such as attention, food, or toys-or by social-negative reinforcement-the removal of an aversive stimulus such as escape from an onerous task. Kurtz et al (2003), for example, found that in a sample of young children (10 months to 5 years old) referred for SIB, 48% of SIB was socially maintained, mostly by social-positive reinforcement. Similar results have been found in older children and adults with mental retardation.…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…Behavioral studies show that SIB is largely socially maintained, either by social-positive reinforcementthe provision of favored stimulus such as attention, food, or toys-or by social-negative reinforcement-the removal of an aversive stimulus such as escape from an onerous task. Kurtz et al (2003), for example, found that in a sample of young children (10 months to 5 years old) referred for SIB, 48% of SIB was socially maintained, mostly by social-positive reinforcement. Similar results have been found in older children and adults with mental retardation.…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…FCT has been demonstrated to be a highly effective treatment for individuals with intellectual disabilities, ranging from mild to profound, who engage in severe problem behaviors such as self-injury and aggression (e.g., Bailey, McComas, Benavides, & Lovascz, 2002;Carr & Durand, 1985;Fisher et al, 1993;Hagopian, Fisher, Sullivan, Acquisto, & LeBlanc, 1998;Kurtz, et al, 2003;Shirley, Iwata, Kahng, Mazaleski, & Lerman, 1997;Wacker et al, 1990). We searched and reviewed the published literature from 1985 to 2009 1 and identified 76 studies employing FCT as a treatment for 235 individuals with intellectual disabilities of varying ages (i.e., 2-34 years old) displaying a wide range of problem behavior (e.g., aggression, disruption, SIB, inappropriate sexual behavior).…”
mentioning
confidence: 99%
“…Thus, the utility of the paired-choice assessment with young children is unknown. Given the considerable amount of research that emphasizes the importance of early identification and intervention, more research on the assessment and treatment of behavior problems in very young children is needed (Kurtz et al, 2003). In the present case study, the reliability and validity of a paired-choice assessment was evaluated for an infant.…”
mentioning
confidence: 99%